How do you convert y=x-2y+x^2y^2 into a polar equation?

1 Answer
Jul 29, 2016

r = root(3)((3sin(t) - cos(t))/(cos(t)^2sin(t)^2))

Explanation:

Converting a rectangular equation to a polar equation is fairly simple, it is accomplished using:

x = rcos(t)
y = rsin(t)

Another useful rule is that since cos(x)^2 + sin(x)^2 = 1:

x^2 + y^2 = r^2cos(t)^2 + r^2sin(t)^2 = r^2

But we won't need that for this problem. We also want to rewrite the equation as:
0 = x - 3y + x^2y^2

And we perform substitution:

0= rcos(t) - 3rsin(t) + r^4cos(t)^2sin(t)^2
0 = cos(t) - 3sin(t) + r^3cos(t)^2sin(t)^2

Now we can solve for r:

-r^3cos(t)^2sin(t)^2 = cos(t) - 3sin(t)

r^3cos(t)^2sin(t)^2 = 3sin(t) - cos(t)

r^3 = (3sin(t) - cos(t))/(cos(t)^2sin(t)^2)

r = root(3)((3sin(t) - cos(t))/(cos(t)^2sin(t)^2))